2023
DOI: 10.3390/f14040676
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of the Transcriptome and Metabolome Reveals the Mechanism of Chinese Fir Seed Germination

Abstract: Chinese fir (Cunninghamia lanceolata (Lamb.) Hook.) is an important plantation tree species in China, and seed germination is a key step in forest tree cultivation. To reveal the gene expression network and molecular mechanisms in the germination of Chinese fir seeds, physiological indexes were measured and transcriptome and metabolome analyses were performed on Chinese fir seeds in four stages of germination (imbibition stage, preliminary stage, emergence stage, and germination stage). All six physiological i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…In our study, KEGG pathway analysis indicated that 13 DEGs were significantly enriched in the phenylpropanoid biosynthesis pathway and 6 DEGs in the flavonoid biosynthesis pathway ( Figure 5 ), implying that phenylpropanoid biosynthesis and flavonoid biosynthesis are the key pathways during GA 3 -induced dormancy release. A similar result was also described by Chen et al. (2023) , who found that the phenylpropanoid biosynthesis and flavonoid biosynthesis pathways had important roles in the seed germination of Chinese fir [ Cunninghamia lanceolat (Lamb.)…”
Section: Discussionsupporting
confidence: 82%
“…In our study, KEGG pathway analysis indicated that 13 DEGs were significantly enriched in the phenylpropanoid biosynthesis pathway and 6 DEGs in the flavonoid biosynthesis pathway ( Figure 5 ), implying that phenylpropanoid biosynthesis and flavonoid biosynthesis are the key pathways during GA 3 -induced dormancy release. A similar result was also described by Chen et al. (2023) , who found that the phenylpropanoid biosynthesis and flavonoid biosynthesis pathways had important roles in the seed germination of Chinese fir [ Cunninghamia lanceolat (Lamb.)…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, in Cinnamomum migao, genes related to carbohydrate and lipid metabolism were predominantly activated after seed coat rupture [64]. Additionally, there was a decrease in total starch and crude oil content during seed germination of Phyllostachys edulis, whereas genes involved in starch metabolism and lipid body degradation pathways were consistently upregulated [65]. These findings align with our own results; however, unlike these studies, we inferred a relationship between starch and lipid release based on our results.…”
Section: Lipids Release May Serve As a Potential Supplement In The Ca...supporting
confidence: 89%
“…In the present study, the length of the roots of mulberry plants decreased significantly with increasing salt concentration, while the decrease in fresh weight was not significant. In addition, seed germination is one of the most important growth and developmental processes in plants; it is extremely sensitive to salt stress and is subjected to the coordinated interactions of multiple genes and metabolites [ 43 ]. Mulberry plants are rich in flavonoids and other secondary metabolites, which play a wide range of roles in defense against biotic and abiotic stresses [ 18 ].…”
Section: Discussionmentioning
confidence: 99%